Hypoglycemia is associated with dementia in elderly patients with type 2 diabetes mellitus: An analysis based on the Korea National Diabetes Program Cohort. (December 2016) - Chin, Sang Ouk; Rhee, Sang Youl; Chon, Suk; Baik, Sei Hyun; Park, Yongsoo; Nam, Moon Suk; Lee, Kwan Woo; Chun, Ki Hong; Woo, Jeong-taek; Kim, Young Seol
Highlights: 6.4% of included subjects experienced hypoglycemia-related events (mean F/U period of 3.4 years). The incidence of dementia was significantly higher in subjects with hypoglycemic events. Hypoglycemic events were associated with dementia following multiple adjustments. The risk of dementia increased commensurate with more frequent hypoglycemic events. Abstract: Aim: Although hypoglycemia is associated with cognitive dysfunction, including dementia, in patients with type 2 diabetes mellitus (DM), the data are equivocal. The purpose of this study was to investigate the association between hypoglycemia, dementia, and other cognitive dysfunctions. Methods: This was a prospective observational study based upon the Korea National Diabetes Program (KNDP). Among the 4540 participants in the KNDP cohort, individuals aged ⩾60 years without any history of hypoglycemia or cognitive dysfunction ( n = 1957) were included. Nationally representative data from the Health Insurance Review and Assessment Service of Korea claim database were used to obtain a more precise determination of patient outcome. Results: During a mean follow-up period of 3.4 ± 0.9 years, 118 subjects experienced hypoglycemia-related events. The incidence of dementia and cognitive dysfunction was 7.5 cases per 1000 person-years (PY) and 0.61 cases per 1000 PY, respectively. In the subjects who experienced hypoglycemic events (relative to those who did not), the incidence of dementia was significantly higher ( P = 0.0139), but the incidence of cognitive dysfunction was not ( P = 0.1106). Hypoglycemic events were associated with dementia (HR, 2.689; 95% CI, 1.080–6.694, P = 0.0335) following multiple adjustments. There was also a significant linear trend toward an increased dementia risk commensurate with an increasing number of hypoglycemic events ( P = 0.0286). Conclusions: Hypoglycemia is significantly associated with the risk of dementia in Korean type 2 DM patients aged ⩾60 years.